Division of labor in epitranscriptomics: What have we learnt from the structures of eukaryotic and viral multimeric RNA methyltransferases?. (27th May 2021) - Graille, Marc
Abstract: The translation of an mRNA template into the corresponding protein is a highly complex and regulated choreography performed by ribosomes, tRNAs, and translation factors. Most RNAs involved in this process are decorated by multiple chemical modifications (known as epitranscriptomic marks) contributing to the efficiency, the fidelity, and the regulation of the mRNA translation process. Many of these epitranscriptomic marks are written by holoenzymes made of a catalytic subunit associated with an activating subunit. These holoenzymes play critical roles in cell development. Indeed, several mutations being identified in the genes encoding for those proteins are linked to human pathologies such as cancers and intellectual disorders for instance. This review describes the structural and functional properties of RNA methyltransferase holoenzymes, which when mutated often result in brain development pathologies. It illustrates how structurally different activating subunits contribute to the catalytic activity of these holoenzymes through common mechanistic trends that most likely apply to other classes of holoenzymes. This article is categorized under: RNA Processing > RNA Editing and Modification RNA Processing > Capping and 5′ End Modifications Abstract : The catalytic subunits (wine red) of several RNA methyltransferases acting on factors involved in protein synthesis require a tight partnership with activating subunits (pink) to be functional. Methyl groups are shown as black stars.